(untitled) (European Journal of Marketing and Economics, 2022)
Employees are an integral part of any organization because of the value they bring, and how they help the organization achieve its goals. Yet, the percentage of employees who are passionate about their jobs and the overall goal of the organization where they work remains in the minority. While workplace factors tend to play a role in determining the extent to which employees are engaged, actively engaged or unengaged, the direct impact on employee engagement remains vague. This paper presents the outcome of a study conducted which evaluates the impact of workplace factors on employee engagement in public sector entity. An online questionnaire was completed by 120 employees of one of UAE public sector entities. Participants were selected through random sampling to ensure fair representation. The primary data was analyzed using structural paths analysis to determine the direct effects of workplace experience as well as workplace conditions on Employee Engagement respectively. The findings indicate that workplace conditions positively influence employee engagement in the public sector entity, while the impact of workplace experience is negative and unsupported in the UAE public entity examined. The implication of these findings is that public sector entities such as the one examined is able to determine the workplace factor to prioritise for sustaining engagement of its employees in order to increase engagement level. This study advances organizational studies in general, particularly the field of employee engagement. The result helps to empirically verify the positive influence of workplace factors such as clarity of work, opportunities at work and support from managers on employee engagement.